Comparative studies on the morphometry and physiology of European populations of the lagoon specialist Cerastoderma glaucum (Bivalvia) - Katarzyna Tarnowska; Maciej Wołowicz; Anne Chenuil; Jean-Pierre Féral (Oceanologia, 2009)
Seasonal changes in the morphometric and physiological parameters of the cockle Cerastoderma glaucum (Bivalvia) from the Baltic Sea (GD), the North Sea (LV), and the Mediterranean Sea (BL) were investigated. The cockles from GD were much smaller than those from other populations due to osmotic stress. The female to male ratios did not differ significantly from 1:1. The northern populations (GD, LV) had a monocyclic reproductive pattern, whereas the southern population (BL) seemed to reproduce throughout the year. Seasonal changes in the contents of biochemical components appeared to be correlated with changes in trophic conditions and the reproductive cycle. Protein content was the highest in spring for all the populations. The highest lipid contents and lowest carbohydrate contents were noted in GD and BL in spring, while no marked differences were noted among seasons in LV (probably because the data from both sexes were pooled). Respiration rates in GD were the highest among the populations, which could have been due to osmotic stress. High metabolic rates expressed by high respiration rates in GD and LV in spring and autumn could have resulted from gamete development (in spring) and phytoplankton blooms (in spring and autumn).